Immunohistochemical Expression of Synaptophysin in the Adult and Developing Cervical and Lumbar Enlargements of the Spinal Cord of Rabbit. - Elgarhy, Ahmed K.; Nomir, Ahmed G.; Ahmed, Ahmed Sayed-; Ibrahim, Madiha S.; Watanabe, Yohei; Arai, Yasuha; Nakaya, Takaaki; Sharaby, Ashraf A. El (Academia Anatomica International, 2017)
Background: The principle findings of synaptophysin immunoreactivity (SynpIR) during the ontogeny of rabbit spinal cord are: At E14, SynpIR precedes in the entire marginal layer especially at the entrance zone of dorsal root and motor neurite outgrowth emerged from the basal plate. At E21, SynpIR is expressed in the motoneurons of ventral and lateral horns of mantle layer growing into the ventrolateral columns of marginal layer. Methods: We found intensely stained thick tracts and diffuse axons among proliferating neuroblasts of mantle layer. The peripheral parts of ventral horns were occupied with closely packed multipolar neurons from which long dendrites departed toward the surface of marginal layer. Results: At E28, pronounced SynpIR presented in the ventral grey horn while the white matter was faintly stained., meanwhile the dorsal horn was more cellular than ventral and lateral horns. Few intensively SynpIR fibers cross the dorsal and ventral commissures. In adult, profuse SynpIR appeared in the entire grey matter, and stained dendrites departed from neurons in the lateral laminae into the adjacent funiculi as finger-like projections. These projections did not reach the surface, so that the outer one-third to onefourth of the funiculi contained little or no SynpIR. In the periphery of ventral horns, we found large multipolar neurons with faintly stained cytoplasm. The white matter and the neuroepithelial cells surrounding the central canal were almost unstained. Conclusion: Synaptophysinis a reliable marker for fiber outgrowth and synapse formation in therabbit spinal cord, and its differential expression levels is specific and almost completed before birth.